Fungicide Resistance Action Committee's (FRAC) Classification Scheme of Fungicides According to Mode of Action - Frederick M. Fishel (EDIS, 2019)
This guide addresses resistance to pesticides and describes the Fungicide Resistance Action Committee's (FRAC) classification of fungicides and bactericides registered for use in Florida by their modes of action. A cross reference of active ingredient common names with corresponding examples of their trade names is also provided.  This document is PI-94, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date January 2006.